2007
DOI: 10.1002/jmv.20910
|View full text |Cite
|
Sign up to set email alerts
|

Detection and molecular characterization of human group C rotaviruses in Okayama Prefecture, Japan, between 1986 and 2005

Abstract: A survey of human group C rotaviruses (CHRVs) was conducted in Okayama Prefecture, Japan, over a period of 19 years between 1986 and 2005. The presence of CHRVs was screened by enzyme-linked immunosorbent assay using CHRV-specific monoclonal antibodies and confirmed by reverse transcription-PCR. Of the 3,722 fecal specimens from sporadic cases of gastroenteritis, 44 specimens (1.2%) were positive for CHRV. The CHRV isolates were detected periodically but continuously, and the rates of positivity changed from o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
12
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 43 publications
2
12
0
Order By: Relevance
“…This observation is in line with a number of publications of group C rotaviruses in sporadic cases of diarrhea with a very low prevalence rate, for instance, 1.2% in Japan [31], 2.3% in Bangladesh [18], 1.8% in Nigeria [28], 1% in Argentina [32], and 0.6% in Hungary [33]. However, several investigators suggested that the patients infected with group C rotaviruses were older (more than 5 years of age) than those infected with human group A rotaviruses [19,31,33]. It is possible that very low incidence of group C rotavirus observed in the present study may be because the patients being enrolled in the study were less than Fig.…”
Section: Discussionsupporting
confidence: 91%
“…This observation is in line with a number of publications of group C rotaviruses in sporadic cases of diarrhea with a very low prevalence rate, for instance, 1.2% in Japan [31], 2.3% in Bangladesh [18], 1.8% in Nigeria [28], 1% in Argentina [32], and 0.6% in Hungary [33]. However, several investigators suggested that the patients infected with group C rotaviruses were older (more than 5 years of age) than those infected with human group A rotaviruses [19,31,33]. It is possible that very low incidence of group C rotavirus observed in the present study may be because the patients being enrolled in the study were less than Fig.…”
Section: Discussionsupporting
confidence: 91%
“…The low prevalence of group C rotavirus infection in this study is in concordance with studies done on similar population, for instance 1% in Argentina, 1% in Spain, 1% in Russia, and 0.4% in Thailand [18,21,36,37]. Other studies also found low prevalence when the study population comprised of children less than 15-years-old, such as 1.8% in Nigeria, 0.6% in Hungary, 1.2% in Japan, and one exception in USA where the prevalence was 4% [5,17,20,22]. Studies that cover adult population showed prevalence of 1.04% in Sweden and 2.3% in Bangladesh [23,24].…”
Section: Discussionsupporting
confidence: 93%
“…Group C rotavirus has been detected in piglets and cattle, and was first detected in humans in 1982 [16]. Since then group C rotaviruses have been detected from both sporadic episodes and the outbreaks of gastroenteritis in Japan, Hungary, Slovenia, US, England, Thailand, Brazil, China, Spain, Bangladesh, Argentina, Sweden, and Nigeria [5,10,15,[17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%
“…These strains were detected as the sole pathogen of diarrhoea in stool specimens from patients (aged 2 months to 9 years) who visited medical facilities. Detection of strains Wu82 and OH567 was described previously (Kuzuya et al, 2007;Wang et al, 2007), and sequence data for some strains are available in GenBank [v508 (VP4, VP6, VP7 and NSP1-5 genes), Wu82 (VP7 and VP6 genes) and OH567 (VP7 gene)]. Therefore, in the present study, sequences of the remaining viral genes were determined for these strains.…”
Section: Discussionmentioning
confidence: 99%
“…Sequence analysis of human GCRV strains from different countries has indicated that the VP7, VP4 and VP6 genes are highly conserved and are considered to belong to a single genotype distinct from those of animal GCRVs, although some lineages have been identified within a human GCRV genotype (Khamrin et al, 2008;Kuzuya et al, 2007; Mitui et al, 2009;Rahman et al, 2005;Schnagl et al, 2004). Like GARVs, genetic classifications based on VP7 (G type) and VP4 (P type) have been proposed for GCRV (Jiang et al, 1999;Martella et al, 2007).…”
Section: Journal Of General Virologymentioning
confidence: 99%